It is a classic Keynesian depression, I would not refrain from the term' - Fernando J. Cardim de Carvalho (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
Fernando Cardim de Carvalho is Professor emeritus for economics at the Federal University of Rio de Janeiro. His research interests include monetary economics and economic policies. He was a consultant for the National Social and Development Bank of Brazil and for the Economic Commission for Latin America and the Caribbean of the United Nations. Fernando Cardim de Carvalho is a co-founder of the Brazilian Keynesian Association and author of more than 160 publications.
Keywords: 330